2022
DOI: 10.1159/000523964
|View full text |Cite
|
Sign up to set email alerts
|

Acute Liver Injury and Acute Liver Failure following Bariatric Surgery

Abstract: Bariatric surgery is the most effective treatment for obesity and improves several manifestations of the metabolic syndrome, including nonalcoholic fatty liver disease. Strict nutritional counseling after bariatric surgery is a key in realizing these outcomes. When postoperative nutrient intake or nutrient uptake is compromised, bariatric surgery can also lead to severe hepatic complications. Here, we describe 3 cases of acute liver injury and acute liver failure caused by bariatric surgery, all with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A combination of malnutrition and non-adherence to nutritional supplements can lead to liver failure. Clinical improvement with conservative treatment and appropriate nutritional support seems to be effective, as recently described by Vandeberg et al and Van Golen et al (51)(52). Consideration of a reversal of malabsorptive BS procedures can be considered in patients presenting with edema or ascites due to hypoalbuminemia in order to improve malnutrition and stabilization of liver disease.…”
Section: The Bidirectional Relationship Between Obesity and Alcoholmentioning
confidence: 85%
“…A combination of malnutrition and non-adherence to nutritional supplements can lead to liver failure. Clinical improvement with conservative treatment and appropriate nutritional support seems to be effective, as recently described by Vandeberg et al and Van Golen et al (51)(52). Consideration of a reversal of malabsorptive BS procedures can be considered in patients presenting with edema or ascites due to hypoalbuminemia in order to improve malnutrition and stabilization of liver disease.…”
Section: The Bidirectional Relationship Between Obesity and Alcoholmentioning
confidence: 85%
“…Factors that may contribute to the process of acute liver failure in patients with nonalcoholic steatohepatitis and metabolic dysfunction associated with steatohepatitis after bariatric surgery include rapid weight loss [40] , nutritional deficiencies [41][42][43][44] , and metabolic changes [41] . In terms of rapid weight loss, there has been no observed consistent relationship between the speed or amount of fat loss and the development of acute liver injury after bariatric surgery [41] .…”
Section: Liver Failurementioning
confidence: 99%
“…In terms of rapid weight loss, there has been no observed consistent relationship between the speed or amount of fat loss and the development of acute liver injury after bariatric surgery [41] . However, one study showed that a weight loss greater than 1.6 kilograms per week was associated with an increase in inflammation and fibrosis of the liver portal system [40] . In addition to this study, one case study suggests that two patients who underwent bariatric surgery and reported a symptom-free postoperative period had no significant weight loss during that period.…”
Section: Liver Failurementioning
confidence: 99%
“…Bariatric surgery is the most effective therapeutic option for weight loss, but there exists access inequality among obese patients [86]. Despite the popularity of bariatric surgery in the treatment of morbid obesity and its related comorbidities, including NAFLD, post-op complications such as acute liver failure necessitating liver transplantation due to associated protein malnutrition and bacterial overgrowth are limiting its use [87,88].…”
Section: Overlapping Management Approachesmentioning
confidence: 99%